Catalytic co-pyrolysis of 5-Amino-1H-Tetrazole assembled with copper and boron powder: Pyrolysis kinetics and reaction mechanism. (15th April 2022) - Chen, Jiu; Li, Bin; Cao, Cheng-Yang; Zhou, Si-Yuan; Xie, Li-Feng; Zhang, Dan
Graphical abstract: Highlights: Catalytic effect of boron powder mainly exerts on latter stages for 5AT pyrolysis. Solution recrystallization method has better modification effect for 5AT pyrolysis. Copper powder can optimize the pyrolysis behaviors for 5AT pyrolysis. Kinetic models for 5AT in each stage have been deduced by model-fitting method. Abstract: As a novel rich nitrogen content material, 5-Amino-1 H -Tetrazole (5AT) has been considerably popularized in the propellants area recently. The pyrolysis is deemed as the prelude of combustion for solid phase 5AT, which plays a crucial role in combustion process and grasping the pyrolysis characteristics will be more beneficial to further explore the combustion properties of 5AT-based propellant. In this paper, several efforts have been made to enhance the pyrolysis behaviors of 5AT, including employing metal particles as catalysts, and modifying the surface treatment method. Due to the calorific value, the boron and copper powder are selected as the potential catalysts. The solvent/non-solvent (S/NS) and solution recrystallization method are compared to explore the impact of these two modification methods. TG-FTIR technique is applied to capture evolved signals of organic compounds to further deduce the most probable decomposition pathway. Moreover, model-free and model-fitting methods are both employed to calculate the kinetic parameters. The results reveal that, for the modified 5AT samples with the same boron powder catalyst, the activation energies and reaction model (all governed by F4) in the initial stage (100–330 °C) are not significantly impacted by these two modification methods. However, during the latter stages (400–750 °C), the catalytic actions of boron powder appear to be more active, and solution recrystallization method exerts better modification effect, the activation energies was reduced 18.3 kJ/mol and 10.9 kJ/mol respectively for the latter stages compared to S/SN method. Also, the reaction model is transformed from nth -dimensional model (D3) to nth -order model (F1) in the third stage. Particularly, the catalytic actions of copper powder results in the simplification of decomposition steps for 5AT, the activation energies was 138.8 kJ/mol and the catalytic effect of which was improved about 25% compared to the catalytic effect of boron powder in the first stage and its reaction model is also found to be changed into F3. It illustrates that copper powder could embody a better catalytic effect than boron powder under the same modification method. The conclusions of this study could provide a worthwhile guidance for the understanding, designs and applications of the 5AT-based propellants.